Experiences and impact of an ethics of research training - García Rupaya, Carmen Rosa (Acta Bioethica, 2012)
This article has the purpose to describe achievements and impact of the ethics of research training at the Interdisciplinary Center for Studies on Bioethics of the University of Chile, which has served as incentive, motivation and guide for professionals which require knowledge, regulations application and dialogue skills to reflect on problems of this discipline. Furthermore, it describes how this knowledge generates a multiplying effect in aspects such as participation in scientific ethical review committees, course organization and the creation and development of research lines, which generate publications by post degree students. It also narrates didactic contents and strategies which could be applied in ethics and bioethics courses for oral health students and concludes mentioning practical applications of this training for teaching, research and institutional development.